การพัฒนาหลักสูตรการทำขนมไทยในท้องถิ่น กลุ่มสาระการเรียนรู้การงานอาชีพ สำหรับนักเรียนชั้นประถมศึกษาปีที่ 6 จังหวัดสุพรรณบุรี - เกษสมบูรณ์ ปานทิพย์; บุญกุศล ทองปาน; เกิดสุวรรณ์ สุพจน์ (วารสารวิชาการศึกษาศาสตร์ ศรีนครินทรวิโรฒ, 2022)
บทคัดย่อ การวิจัยครั้งนี้มีความมุ่งหมายเพื่อพัฒนาหลักสูตรการทำขนมไทยในท้องถิ่น กลุ่มสาระการเรียนรู้ การงานอาชีพ สำหรับนักเรียนชั้นประถมศึกษาปีที่ 6 จังหวัดสุพรรณบุรี มีขั้นตอนการพัฒนาหลักสูตร 4 ขั้นตอน ดังนี้ 1)การศึกษาข้อมูลขั้นพื้นฐาน 2)การพัฒนาหลักสูตร 3)การทดลองใช้หลักสูตร 4)การประเมินผลและปรับปรุงหลักสูตร กลุ่มตัวอย่างที่ใช้ในการทดลอง ได้แก่ นักเรียนชั้นประถมศึกษาปีที่ 6 โรงเรียนวัดสระประทุม อำเภอเมือง จังหวัดสุพรรณบุรี ภาคเรียนที่ 2 ปีการศึกษา 2563 จำนวน 16 คน ได้มาจากการสุ่มแบบกลุ่ม ใช้โรงเรียนเป็นหน่วยการสุ่ม เครื่องมือที่ใช้ในการวิจัยได้แก่ แบบสัมภาษณ์ แบบสอบถาม หลักสูตรการทำขนมไทยในท้องถิ่น แผนการจัดการเรียนรู้ แบบทดสอบวัดผลสัมฤทธิ์ทางการเรียน แบบประเมินทักษะการทำขนมไทยในท้องถิ่น และแบบประเมินความพึงพอใจต่อหลักสูตร วิเคราะห์ข้อมูล โดยใช้ค่าสถิติพื้นฐาน ได้แก่ ค่าความถี่ ร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน ค่าสถิติทดสอบ คือ การทดสอบค่าที และการวิเคราะห์เนื้อหา ผลการวิจัยพบว่า 1) การศึกษาข้อมูลพื้นฐานจากการสอบถามและสัมภาษณ์ผู้ที่เกี่ยวข้องมีความต้องการให้พัฒนาหลักสูตร 2) การพัฒนาหลักสูตรมีความสอดคล้องและเหมาะสมมีค่าดัชนีความสอดคล้อง (IOC)เท่ากับ 1.00 3) การทดลองใช้หลักสูตร พบว่า นักเรียนให้ความสนใจและให้ความร่วมมือปฏิบัติกิจกรรมเป็นอย่างดี 4) ผลการประเมินพบว่าผลสัมฤทธิ์ทางการเรียนของนักเรียนหลังใช้หลักสูตรสูงกว่าก่อนใช้หลักสูตรอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 ทักษะการทำขนมไทยในท้องถิ่นในภาพรวมอยู่ในระดับดี นักเรียนมีความพึงพอใจต่อหลักสูตรในภาพรวมอยู่ในระดับมาก และปรับปรุงหลักสูตรในเรื่องของเวลาในการจัดกิจกรรมการเรียนรู้และสื่อการเรียนรู้ คำสำคัญ: การพัฒนาหลักสูตร, ขนมไทย, ภูมิปัญญาท้องถิ่น ABSTRACT This research study aimed to develop the curriculum of local Thai desserts-making in occupations learning for primary 6 students in Suphanburi Province. For a procedure of the curriculum development, there were four steps as follows: 1) the study of fundamental information 2) the curriculum development 3) the curriculum trial 4) the assessment and improvement of the curriculum. The participants of this research study were 16 students who are in primary 6, semester 2, the academic year 2020, Wat Sa Pratum School, Muang District, Suphanburi Province. Cluster Random Sampling was used as a sampling method in this study, the school was a random sampling unit. In this research study, the tools that were used to collect data were interview form, questionnaire, the curriculum of local Thai dessert-making, lesson plan, an achievement test, an evaluation form of operational skill for local Thai dessert-making, and the satisfaction assessment form toward the curriculum. The statistical data that was used for data analysis were frequency, percentage, mean, standard deviation, the dependent samples t-test, and the content analysis. The findings of the research study were as follows: 1) for the study of fundamental information with relevant people by using questionnaires and interviewing, they required developing the curriculum, 2) for the curriculum development, it was consistent and appropriate with an Index of Item Objective Congruence (IOC) of 1.00, 3) for the curriculum trial, students interested, focused, and cooperated in the activities as well, and 4) the evaluation results found that the achievement of students after taking the course was higher than before taking the course with the statistical significance at the .05 level. The operational skills for local Thai dessert-making of students were good overall. The satisfaction of students toward the curriculum for local Thai dessert-making; overall, it was at a high level. Furthermore, the curriculum should be improved in terms of the time for learning activities and instructional media. Keywords: Curriculum Development, Thai Desserts, Local Wisdom